Vector Control of VSC HVDC System under Single Line to Ground Fault Condition - Prabodha Kumar Rath; Kanhu Charan Bhuyan (International Journal of Applied Power Engineering (IJAPE), 2018)
This paper proposes a model of a VSC (voltage source converter) based Back to Back HVDC system and its control technique under fault condition. From the mathematical model of the system relationship between the controlling and the controlled variables is determined to control the system parameters. An appropriate vector control technique is used to control active and reactive power and to maintain DC link voltage. The proposed controlling unit consists of outer control loop and inner control loop which effectively damped out the system oscillation and maintains the system stability. The validity of the model and the feasibility of the control method have been proved by the simulation results. In this paper the system performance is studied under fault condition is studied.